30 things every woman should have and should know by the time she's 30 - Redmond, Pamela (Hyperion, 2012)
Featuring essays from celebrities and prominent women, a guide drawn from a list that "Glamour" published fifteen years ago presents the must-haves and must-knows for women who have reached the milestone of turning thirty.